KEADILAN DAN KEPASTIAN HUKUM: MENYOAL KONSEP KEADILAN HUKUM HANS KELSEN PERSPEKTIF “AL-‘ADL” DALAM AL-QUR’AN - Mukhlishin Mukhlishin; Sarip Sarip (Universitas Muhammadiyah Mataram, 2020)
Justice as an ideal and legal objective can be realized through law. Hans Kelsen said, justice is the legality that the benchmark lies in its validity according to positive law. This study aims to describe the concept of fairness according to Hans Kelsen's philosophy and relevance to the concept of al-Adl al-Qur; an. This study is a literature review, with a philosophical approach - Usul Fiqh. The results of the study show that the concept of al-'Adlu in the Qur'an has a wider scope from a human perspective. Al-'Adl has the substance of absolute justice only possessed by the Divine, revealed to the Prophet Muhammad, the Prophet's behavior is justice (prophetic philosophy). Subjective justice, which is essentially an attempt to fulfill positive legal certainty as a benchmark, is completely untenable. Because, justice is not limited to validity according to positive law but justice must pay attention to the meaning of lafadz al-'Adl is a transcendental basis that is absolute for human benefit. The concept of